2019
DOI: 10.5534/wjmh.180045
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Sleep Disorders, and Sexual Dysfunction

Abstract: Good sleep is necessary for good health. Sleep health is increasingly recognized as important for physical and mental health by both the medical profession and the general public, and there is great interest in how to avoid and treat sleep disorders and problems. Recent research indicates that insufficient sleep, disrupted sleep, and sleep disorders affect many aspects of human health including sexual function. In fact, patients with urological disorders or erectile dysfunction (ED) may have a sleep disorder t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 149 publications
1
88
0
5
Order By: Relevance
“…We could hypothesize that hormonal secretion in short sleepers might become chronically subclinically disturbed, as a result of sleep debt. Furthermore, short sleep could impair fertility from a behavioral point of view, as it has been linked to sexual dysfunction (52) and lower odds of partnered sexual activity in a large study (53). Short sleep is also significantly associated with chronic conditions and diseases, such as obesity, type 2 diabetes, cardiovascular diseases, and depression, which might by themselves influence fertility (5,6,54).…”
Section: Discussionmentioning
confidence: 99%
“…We could hypothesize that hormonal secretion in short sleepers might become chronically subclinically disturbed, as a result of sleep debt. Furthermore, short sleep could impair fertility from a behavioral point of view, as it has been linked to sexual dysfunction (52) and lower odds of partnered sexual activity in a large study (53). Short sleep is also significantly associated with chronic conditions and diseases, such as obesity, type 2 diabetes, cardiovascular diseases, and depression, which might by themselves influence fertility (5,6,54).…”
Section: Discussionmentioning
confidence: 99%
“…There is also data which support our findings that patientd with erectile dysfunction might report poorer quality of sleep. 51 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that sleep disorders may influence testosterone production (710). Current guidelines recommend distinguishing between organic and functional causes of hypogonadism.…”
Section: Introductionmentioning
confidence: 99%